2013
DOI: 10.1007/s00005-013-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCL25 Antibody Prolongs Skin Allograft Survival by Blocking CCR9 Expression and Impairing Splenic T-Cell Function

Abstract: Chemokines, by virtue of their ability to recruit immune cells into allografts, play critical roles in acute transplantation rejection. CCR9 and its ligand, CCL25, is one of the key regulators of thymocyte migration and maturation in normal and inflammatory conditions. Moreover, several studies have revealed that high expression of CCR9 and CCL25 participated in many kinds of diseases. However, the role of CCR9 in allograft rejection is still unclear. In this study, we established a murine skin transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…CCR9, a chemokine receptor that mediates the chemotaxis of inflammatory cells in combination with CCL25 (a member of CC chemokine superfamily), was identified and has recently received recognition1034. CCR9 has been documented in various tissues, such as the small intestine, liver, arthritic tissues, and the brain, as mainly mediating inflammatory diseases1314151635. In the cardiovascular system, CCR9 was first found to be associated with the pathophysiology of atherosclerosis, and inhibition of CCR9 by RNA interference in apoE-deficient mice significantly retarded the development of atherosclerosis18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCR9, a chemokine receptor that mediates the chemotaxis of inflammatory cells in combination with CCL25 (a member of CC chemokine superfamily), was identified and has recently received recognition1034. CCR9 has been documented in various tissues, such as the small intestine, liver, arthritic tissues, and the brain, as mainly mediating inflammatory diseases1314151635. In the cardiovascular system, CCR9 was first found to be associated with the pathophysiology of atherosclerosis, and inhibition of CCR9 by RNA interference in apoE-deficient mice significantly retarded the development of atherosclerosis18.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, CCR9 was found to be involved in the migration and development of T cells in the thymus12. However, in recent years, emerging evidence has shown that CCR9 participates in several diseases131415161718. Some studies have been conducted to interfere with the CCR9/CCL25 axis and test its effectiveness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies demonstrated that CCR9 is highly expressed in the colon, small intestine and several other tissues involved in the development and maturation of T cells, macrophages and dendritic cells (DCs) ( 4 9 ). CCR9 signaling may therefore have an influence on processes, including inflammatory responses and transplantation rejection ( 10 12 ). Furthermore, CCR9 has been demonstrated to influence cancer cell migration, proliferation and drug resistance ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…CCL25 is expressed in thymus and small intestinal epithelium [35] and regulates trafficking of gut tropic effect or T cells via upregulation of the integrin homing receptor α4β7, which interacts with MadCAM-1 on intestinal microvascular endothelium [36, 37]. Accumulating evidence had shown that the CCR9/CCL25 axis participated in a variety of disease processes [38, 39]. The levels of colonic CCL25 had been shown to increase in both Crohn’s disease and ulcerative colitis, and pharmacological inhibitors of CCR9 prevented the development of ulcerative colitis in an experimental model [40].…”
Section: Discussionmentioning
confidence: 99%